PENGARUH KEGIATAN KEPRAMUKAAN TERHADAP PENGETAHUAN KEWARGANEGARAAN (CIVIC KNOWLEDGE) MAHASISWA DI UNIVERSITAS MUHAMMADIYAH PURWOKERTO - Efi Miftah Faridli (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2018)
This research entitled Influence of Scouting Activity on Civic KnowledgeStudent at Muhammadiyah University of Purwokerto. The purpose is to studyhow the influence of Scouting Activities at Muhammadiyah University ofPurwokerto to Knowledge of student’s citizenship. The method used isdescriptive research method, weighting score (Weighted Mean Score),correlation test r and t test analysis. This research was conducted to membersof Scout Movement active in Front Cluster Banyumas 08.2683-08.2684University of Muhammadiyah Purwokerto counted 41 people. Based on theresults of data processing known that Scouting Activity effect of 75.8%. on theKnowledge of Citizenship, the remaining 24.2% is influenced by other factorsnot examined. Suggestion from the researcher, it is expected to be the input forthe implementers of Scouting activities in this case the Front Line so that betterin preparing this activity should be more coordinated with the related parties,such as: the trainers who must be more proactive in this activity, the committeeas a whole to improve the quality of its work in preparing these activities.Keywords: scouting, scout movements, civic knowledge